The effects of different concentration of glucose-sucrose syrup on the quality of glazed papaya - Cordova, Wispy B.
The effects of varying proportions of glucose-sucrose for glazing syrup on the qulaity of glazed papaya were studied using 20:80 (Sample A); 30:70 (Sample B); and 40:60 (Sample C).